2021
DOI: 10.1177/10915818211048151
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Expression Profile of Antibiotic-Induced Thrombocytopenia Using the Japanese Adverse Drug Event Report Database

Abstract: Drug-induced thrombocytopenia (DITP) can be triggered by antibiotics; however, the details remain unclear. Here, we evaluated the expression profiles of DITP using the Japanese Adverse Drug Event Report (JADER) database. We analyzed reports of DITP between April 2004 and January 2021 from the JADER database. The reporting odds ratio (ROR) and 95% confidence interval (CI) were used to detect DITP signals. Factors thought to affect DITP, such as male sex and an age of at least 60 years, were added as covariates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Evaluating thrombocytopenia, it is already known that women have a larger platelet count than men [ 25 ]. A recent Japan study on antibiotic-induced thrombocytopenia reports that there is a higher drug-induced thrombocytopenia in male patients treated with six different drugs, compared with females [ 26 ], as we report for topoisomerase inhibitor and DNA binding drugs. In addition, we observed that the female sex is a negative predictor of dysgeusia in those undergoing topoisomerase inhibitor, growth inhibitor, and monoclonal antibody chemotherapy.…”
Section: Discussionsupporting
confidence: 77%
“…Evaluating thrombocytopenia, it is already known that women have a larger platelet count than men [ 25 ]. A recent Japan study on antibiotic-induced thrombocytopenia reports that there is a higher drug-induced thrombocytopenia in male patients treated with six different drugs, compared with females [ 26 ], as we report for topoisomerase inhibitor and DNA binding drugs. In addition, we observed that the female sex is a negative predictor of dysgeusia in those undergoing topoisomerase inhibitor, growth inhibitor, and monoclonal antibody chemotherapy.…”
Section: Discussionsupporting
confidence: 77%
“…The mechanisms of thrombocytopenia associated with many drugs remain unknown, which creates additional challenges in managing DIT clinically. 12,13 Therefore, the identification of drugs associated with thrombocytopenia is crucial before establishing an appropriate management plan. Certain cases of DIT can only be detected through long-term monitoring, and so clinical trails might not be the best study design.…”
mentioning
confidence: 99%
“…Yuki Asai et al analyzed the relationship between antibacterial drugs and thrombocytopenia using JADER, and revealed the profiles of DIT and 12 antibiotics. 18 Emily Jane Woo et al discovered the increased risk of thrombocytopenia associated with the Ad.26.COV2.S COVID-19 vaccine based on Vaccine Adverse Event Reporting System (VAERS) data. 19 Go Ando et al used both JADRS and FAERS to identify an association between ganciclovir and thrombocytopenia.…”
mentioning
confidence: 99%
See 2 more Smart Citations